2018
DOI: 10.5114/pjp.2018.76699
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of androgen receptor expression in HER2-positive and triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) and HER2-positive breast cancer are more aggressive than other subtypes of breast cancer. Due to the limited number of treatment alternatives and the absence of target receptors in TNBC, and because of progression in the HER2-positive group despite targeted treatments, new treatment targets and therapeutic combinations are required. In this context, the present study aims to evaluate the prognostic importance of immunohistochemical androgen receptor (AR) expression in HER2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
3
9
0
Order By: Relevance
“…Breast cancer (BC) is referred to as type of mixed tumors with different actions, prognosis, and difficult to treat (Noman et al, 2016) Many studies reported that about 15% of BC patients are TNBC positive. This type of cancer is more aggressive than other BC types and has poorer prognosis compared to other BC types (Speers et al, 2017;Kucukzeybek et al, 2018) Recent studies revealed that BC heterogeneity extends to the classic IHC-based subtypes of ER, PR, and HER2 receptors. (Gradishar et al, 2016;Kurozumi et al, 2016) Nowadays, new treatment methods are suggested for TNBC according to new biomarkers and gene expression profile (Burstein et al, 2015;Sarin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer (BC) is referred to as type of mixed tumors with different actions, prognosis, and difficult to treat (Noman et al, 2016) Many studies reported that about 15% of BC patients are TNBC positive. This type of cancer is more aggressive than other BC types and has poorer prognosis compared to other BC types (Speers et al, 2017;Kucukzeybek et al, 2018) Recent studies revealed that BC heterogeneity extends to the classic IHC-based subtypes of ER, PR, and HER2 receptors. (Gradishar et al, 2016;Kurozumi et al, 2016) Nowadays, new treatment methods are suggested for TNBC according to new biomarkers and gene expression profile (Burstein et al, 2015;Sarin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, patients treated with first-line trastuzumab, AR+ tumors had longer PFS (15.8 vs. 8.2 months, P = 0.005) and 5-year OS rate (66.2 vs. 26.2%, P = 0.009) compared with AR-negative subjects ( 48 ). In addition, a study involving 111 operated patients with BC revealed no significant correlations between AR expression and prognostic values in the HER2+ group ( 49 ). On the contrary, a notable finding of a meta-analysis, including three studies with 358 patients, revealed the worse clinical outcome conferred by AR expression in patients with HER2+ER-(Her2-enriched) BC ( 44 ).…”
Section: The Clinical Relevance Of Ar In Bcmentioning
confidence: 99%
“…[9][10][11] Nevertheless, the role of AR expression as a prognostic factor in TNBC is still controversial. In some trials, patients with TNBC with AR expression had a better prognosis [12][13][14][15][16][17][18][19][20] ; however, others indicated that AR positivity was associated with poor prognosis. [21][22][23][24][25][26] In addition, in several studies, [27][28][29][30][31][32][33][34][35][36][37][38] it was illustrated that AR expression did not correlate with the prognosis of TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 In a previous meta-analysis, it was confirmed that AR positivity was associated with a lower risk of disease recurrence. 41 However, studies [12][13][14][15][21][22][23]27,28,32,[34][35][36][37][38] assessing the connection of AR expression and its prognostic value have recently been published, and have added to the inconsistent evidence. According to the Cochrane Handbook for Systematic Reviews of Interventions, 42 the meta-analysis should be updated every 2 years.…”
Section: Introductionmentioning
confidence: 99%